2019
DOI: 10.1021/acsami.9b10394
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Power Factor and Electron Mobility in n-Type Bi2Te3x%Cu Stabilized under Excess Te Condition

Abstract: The thermoelectric (TE) community has mainly focused on improving the figure of merit (ZT) of materials. However, the output power of TE devices directly depends on the power factor (PF) rather than ZT. Effective strategies of enhancing PF have been elusive for Bi2Te3-based compounds, which are efficient thermoelectrics operating near ambient temperature. Here, we report ultrahigh carrier mobility of ∼467 cm2 V–1 s–1 and power factor of ∼45 μW cm–1 K–2 in a new n-type Bi2Te3 system with nominal composition Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 64 publications
3
35
2
Order By: Relevance
“…Studies have shown that the two-step sintering technology is an effective method, which can control the existence and distribution of element inhomogeneity, so that the carrier transport and phonon transport have a special directionality. This has a specific guiding significance for other thermoelectric material systems with similar characteristics ( Cha et al, 2019 ; Pan et al, 2019 ).…”
Section: Adjustments Of Carrier Parameters To Improve Ztmentioning
confidence: 85%
See 1 more Smart Citation
“…Studies have shown that the two-step sintering technology is an effective method, which can control the existence and distribution of element inhomogeneity, so that the carrier transport and phonon transport have a special directionality. This has a specific guiding significance for other thermoelectric material systems with similar characteristics ( Cha et al, 2019 ; Pan et al, 2019 ).…”
Section: Adjustments Of Carrier Parameters To Improve Ztmentioning
confidence: 85%
“…Most high-performance thermoelectric materials are heavily doped semiconductors, and the optimal carrier concentration n opt varies with ( m*T ) 3/2 . Therefore, n opt can also be achieved by tuning the effective quality m d * ( Cha et al, 2019 ). According to m d * = N v 2/3 m b * , degeneracy ( N v ) and effective mass ( m b * ) play a decisive role in m d * .…”
Section: Improvement Of Effective Qualitymentioning
confidence: 99%
“…The resulting increases in the Seebeck coefficient and electrical conductivity enhanced the ZT value. Cha et al 15 reported that addition of Cu to Bi 2 Te 3 compound increases the carrier concentration and mobility as well as the electrical conductivity, and thus the ZT value.…”
Section: Introductionmentioning
confidence: 99%
“…reported improved reproducibility and performance in Cu-incorporated Bi 2 Te 3 . [3][4][5][6][7][8] However, the incorporated Cu was found at different sites such as intercalation or substitution sites within Bi 2 Te 3 lattice, and could even be precipitated. [9][10][11][12][13][14][15][16][17] The intercalation mechanism in Bi 2 Te 3 -based systems were also investigated with different dopants like Sn and CuI.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] The improved reproducibility and enhanced zT was reported in Cu-intercalated n-type ternary Bi 2 Te 2.7 Se 0.3 . 5 Recently, doping behavior of excess Cu in the ternary Bi 2 Te 2.7 Se 0.3 was observed via atomicscale chemical mapping. 17 Excess Cu doping behavior in ternary Bi 2 Te 2.7 Se 0.3 has been directly demonstrated by atomic-scale chemical mapping: excessive Cu atoms in Bi 2 Te 2.7 Se 0.3 occupied (1) Bi-site at a low content of 0.2 at % (Cu 0.01 Bi 2 Te 2.7 Se 0.3 ) and (2) three crystallographic sites (Bi, Te, (1) and Te (2) ) and van der Waals gap (intercalation) at high content of 1.2 at% (Cu 0.06 Bi 2 Te 2.7 Se 0.3 ).…”
Section: Introductionmentioning
confidence: 99%